Prevalence of Obesity, Prediabetes, and Diabetes in Sexual Minority Men: Results From the 2014 Behavioral Risk Factor Surveillance System. Issue 1 (February 2018) - Newlin Lew, Kelley; Dorsen, Caroline; Long, Thomas
Purpose: The purpose of this study is to assess the prevalence and related odds ratios for obesity, prediabetes, and diabetes in sexual minority men (SMM) in relation to straight men. Methods: A secondary analysis of 2014 Behavioral Risk Factor Surveillance System data from 19 states (n = 53 542) was conducted. Weighted means and standard errors were computed to estimate prevalence rates of obesity, prediabetes, and diabetes across male sexual orientation groups, respectively. Unadjusted and adjusted (demographics, depression, and health care access factors) weighted logistic regression models were developed. Results: Obesity prevalence was lower in gay men relative to straight men with logistic regression modeling indicating gay men were significantly less likely to be obese, relative to their straight counterparts, in the unadjusted and adjusted models. In terms of prediabetes, rates were low across all sexual orientation groups with no significant differences observed. Yet bisexual men, relative to straight men, had higher rates of diabetes with significantly increased odds for the disease in both the unadjusted and adjusted models. Conclusion: Findings indicate gay men have reduced risk for obesity while bisexual men may have increased diabetes burden. Across all male sexual orientation groups, prediabetes prevalence was low, suggesting the need for more aggressive prediabetes screening. Additional research is necessary to confirm the findings.